2015
DOI: 10.1371/journal.pone.0122312
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Data and Early Postoperative Outcomes after Minimally Invasive Lumbar Interbody Fusion: Results of a Prospective, Multicenter, Observational Data-Monitored Study

Abstract: Minimally invasive lumbar interbody fusion (MILIF) offers potential for reduced operative morbidity and earlier recovery compared with open procedures for patients with degenerative lumbar disorders (DLD). Firm conclusions about advantages of MILIF over open procedures cannot be made because of limited number of large studies of MILIF in a real-world setting. Clinical effectiveness of MILIF in a large, unselected real-world patient population was assessed in this Prospective, monitored, international, multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…After assessment of full text, twenty-five studies fulfilled the eligibility criteria and were included for qualitative analysis. Boissiere et al [47], Kok et al [54], and Pereira et al [60] were excluded for the quantitative analysis because of an overlap in study population with Barrey et al [46], Kok et al [55], and Franke et al [68], respectively. Tables 1 and 2 show overall study and patient characteristics, respectively.…”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…After assessment of full text, twenty-five studies fulfilled the eligibility criteria and were included for qualitative analysis. Boissiere et al [47], Kok et al [54], and Pereira et al [60] were excluded for the quantitative analysis because of an overlap in study population with Barrey et al [46], Kok et al [55], and Franke et al [68], respectively. Tables 1 and 2 show overall study and patient characteristics, respectively.…”
Section: Selected Studiesmentioning
confidence: 99%
“…Only four studies [49,60,68,69] reported use of a published study protocol. Ghogawala et al [49], Franke et al [68], and Kanter et al [69] provided data at all follow-up intervals and thorough description of their primary and secondary outcome selection.…”
Section: Outcome Reporting Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this trend, operative techniques, surgical devices, and intraoperative monitoring equipment have improved and have resulted in reduced peri‐procedural complication rates. Minimally invasive spinal surgery (MIS) is gaining more relevance, especially because the surgical tissue trauma is significantly reduced when compared to open surgical procedures. MIS performed by experienced surgeons have shown improved clinical outcomes and lower perioperative morbidities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the advantages of MIS include minimized intraoperative blood loss, reduced perioperative morbidity, and lower infection rates. It has been suggested, but for the time being remains uncertain, that these surgical advantages will translate into faster recoveries and earlier return of function in the patients treated.…”
Section: Introductionmentioning
confidence: 99%